Effect of labour market conditions on reporting of limiting long-term illness and permanent sickness in England and Wales. Issue 3 (June 1997) - Haynes, R; Bentham, G; Lovett, A; Eimermann, J
Abstract : STUDY OBJECTIVE: To identify any bias in the reporting of limiting long term illness and permanent sickness due to labour market conditions, and show the absence of the effect in mortality rates. DESIGN: A geographically based study using data from the 1991 census. Standardised ratios for mortality and long term illness in people aged 0-64 years and permanent sickness in people of working age were compared with Carstairs deprivation scores in multilevel models which separated the effects operating at three geographical scales: census wards, travel to work areas, and standard regions. Holding ward and regional effects constant, variations between travel to work areas were compared with long term unemployment rates. SETTING: Altogether 8690 wards and 262 travel to work areas in England and Wales. MAIN RESULTS: Variations in mortality, limiting long term illness, and permanent sickness were related to Carstairs deprivation scores and standard region. With these relationships controlled, limiting long term illness and permanent sickness were significantly related to long term unemployment levels in travel to work areas, but mortality was not affected. Self reported morbidity was more sensitive to variations in long term unemployment rates in conditions of high social deprivation than in affluent populations. CONCLUSIONS: Limiting long term illness and permanent sickness measures may reflect a tendency for higher positive response in difficult labour market conditions. For average social deprivation conditions, standardised limiting long term illness for people aged 0-64 years was 20% higher in travel to work areas where employment prospects were relatively poor compared with areas with relatively good employment prospects. This casts doubt on the use of limiting long term illness as an indicator of objective health care needs for resource allocation purposes at national level.